2023
DOI: 10.1021/acs.macromol.3c01107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chain Architecture on the Structure, Dynamics, and Rheology of Thermoresponsive Poloxamer Hydrogels and Associated Blends

Joanna M. White,
Adelyn A. Crabtree,
Frank S. Bates
et al.

Abstract: Poloxamers, ABA triblock polymers composed of a poly(propylene oxide) (PPO) midblock (B) and poly(ethylene oxide) end blocks (A), are widely studied for biomedical applications. Aqueous poloxamer 407 (P407) undergoes a solution-to-gel transition with increasing temperature, driven by the formation and ordering of micelles onto periodic lattices; however, the gel temperature and resulting modulus have limited tunability. Here, reverse P407 (RP407), a BAB polymer of the same composition and molar mass but with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 99 publications
0
0
0
Order By: Relevance
“…All SAXS profiles exhibited Bragg peaks derived from the micelle packing phase. Various micelle packing structures, including a face-centered cubic (FCC) structure and a body-centered cubic (BCC) structure, have been reported for poloxamer gels. ,, The structure of ordered micelle packing can be characterized based on the relative peak position ( q / q 0 ) of each peak position q with respect to the fundamental peak position q 0 . Table S1 shows the relative peak positions of FCC and BCC structures and the Miller index ( hkl ) of the corresponding lattice planes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All SAXS profiles exhibited Bragg peaks derived from the micelle packing phase. Various micelle packing structures, including a face-centered cubic (FCC) structure and a body-centered cubic (BCC) structure, have been reported for poloxamer gels. ,, The structure of ordered micelle packing can be characterized based on the relative peak position ( q / q 0 ) of each peak position q with respect to the fundamental peak position q 0 . Table S1 shows the relative peak positions of FCC and BCC structures and the Miller index ( hkl ) of the corresponding lattice planes.…”
Section: Resultsmentioning
confidence: 99%
“…It should be mentioned that the gel strength of P407 ( G′ at 40 °C) decreased with increasing ACE concentration (Figure ). White et al reported the transition of micelle packing structure from FCC to BCC in 25 wt % P407 gels accompanied by a slight increase in P407 gel strength. In the present study, the micelle packing structure of ACE-loaded P407 gels changed from FCC to BCC, although the gel strength was weakened with increasing ACE concentration.…”
Section: Discussion On the Effect Of Ace On The Phase Behavior Of P407mentioning
confidence: 99%
See 1 more Smart Citation
“…The reverse poloxamer (RP407) showed improved gelation properties compared to P407, which is relevant for applications such as drug delivery and protein stabilization. Mixing P407 and RP407 altered the size and packing of micelles, providing customized gelation behavior for various biomedical applications [ 104 ].…”
Section: Introductionmentioning
confidence: 99%